Commentary on Information Technology Act - "Gupta, Apar" (Gurgaon, 2016)
Commentary on Information Technology Act-Along with Rules, Regulations, Orders, Guidelines, Reports and Policy Documents: 3rd edition The Information Technology Act, 2000 was enacted to give effect to the United Nations General Assembly resolution adopting the Model Law on Electronic Commerce. It was enacted with a view to give a fillip to the growth of electronic transactions, to provide a legal framework, and to prevent computer based crimes in India. The IT Act was amended in 2008 to address contemporary issues and changing nature of cyber-crimes such as publishing sexually explicit material in electronic form, video voyeurism, leakage of data by intermediary, phishing and identity theft.
Keywords: Law